Great Wolf and the Good Woodsman - Hoover, Helen; Bowen, Betsy; ebrary, Inc. (Minneapolis : University of Minnesota Press, 2005)
The miracle of Christmas permits the animals to work together as friends, despite their fear of the Great Wolf, and to rescue their beloved woodsman.
Electronic reproduction.
Keywords: Wolves -- Juvenile fiction; Wolves -- Fiction; Christmas stories; Animals -- Fiction; Electronic books